UJI ANTIBAKTERI Lasianthus (RUBIACEAE) SEBAGAI TUMBUHAN BERKHASIAT OBAT DAN UPAYA PERBANYAKANNYA - Purwantoro, R. Subekti; Siregar, Hartutiningsih-M.; Sudarmono, Sudarmono; Praptiwi, Praptiwi (Buletin Kebun Raya, 2010)
Lasianthus, a member of the family Rubiaceae has potential for medicinal plants. The aims of the research were to find out the potential antibacterial activity of Lasianthus leaf extract and to investigate the effectiveness of plant propagation by stems cutting. The species tested were Lasianthus laevigatus Blume, L furcatus (Miq.) Bremek and L. cf. obscurus Blume. The extracted leaves in n-hexana, ethyl acetate and methanol were tested in vitro against Staphylococcus aureus and Escherichia coil activities that grown on medium of Mueller-Hinton agar. The methanol extracts of each plant material showed significant antibacterial activities on S. aureus and E. coll. Antibacterial activity increased with increasing concentration of the extracts. Plant propagation by stems cutting were done as a first step of conservation effort for respective species. Stems cutting of L. laevigatus, L. purpureus, L. furcatus, L. acuminatus, L rhinocerotis. and L. cf. obscurus with length of 10 cm were applied with Rotoon F to stimulate root growth. The result of plant propagation research showed that only the stems cutting of L. cf. obscurus grew well although roots did not grow until 4 months.